2006
DOI: 10.1097/01.smj.0000240625.27772.79
|View full text |Cite
|
Sign up to set email alerts
|

Serum Leptin Levels in Rheumatoid Arthritis and Relationship with Disease Activity

Abstract: Even though serum leptin levels were found to be significantly higher in RA patients than in control subjects in this study, there was no correlation between serum leptin levels and TNF-alpha levels, clinical and laboratory parameters of disease activity. However serum leptin levels positively correlated with BMI in both patient and control groups. In RA, circulating leptin levels do not seem to reflect disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 34 publications
3
26
0
1
Order By: Relevance
“…Most of the previous studies showed the serum levels of several adipokines in only around 50 patients (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). They indicated that the serum resistin (12,13,25), leptin (14-16, 23, 25) and adiponectin (14,(22)(23)(24)(25) levels are higher in RA patients than in healthy controls, while negative results (14,(17)(18)(19)(20)24) were also reported.…”
Section: Discussionmentioning
confidence: 92%
“…Most of the previous studies showed the serum levels of several adipokines in only around 50 patients (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). They indicated that the serum resistin (12,13,25), leptin (14-16, 23, 25) and adiponectin (14,(22)(23)(24)(25) levels are higher in RA patients than in healthy controls, while negative results (14,(17)(18)(19)(20)24) were also reported.…”
Section: Discussionmentioning
confidence: 92%
“…However, serum levels of leptin seem to be higher than the levels in synovial fluid (44). Although leptin is positively correlated with body fat content (46,50), a correlation between plasma concentration of leptin, body mass index (BMI) (46)(47)(48)50,51), and markers of inflammation is still debated (47)(48)(49)(50)(51)(52). An interesting feature is the finding that serum levels of leptin are higher in active RA than in less-active RA (51), and differences in leptin levels between plasma and synovial fluid were greater in nonerosive than in erosive arthritis (44).…”
Section: Adiponectin In Ramentioning
confidence: 91%
“…In short, there are several potential explanations for these differing results among these studies: first, the relatively small sample size may not precisely represent the larger patients; secondly, the baseline characteristics such as disease duration, age, race and BMI can be inconsistent, which may affect the expression level of leptin; thirdly, patients with other co-existing autoimmune diseases cannot be excluded from studies, which could be potential confounding factors; and fourthly, different measurement methods of leptin levels, such as radioimmunoassay [20,37,40,100] and enzyme-linked immunosorbent assay (ELISA), may also cause deviation [8,23,30]. In addition, discrepancies in leptin levels in RA patients could be due to different treatments that intervene with the endocrine system, which usually complicates human experimental researches.…”
Section: Leptin Levels In Serum Synovial Fluid and Synovial Tissue Amentioning
confidence: 99%